KORELASI KEPRIBADIAN GURU DAN AKHLAK SISWA DENGAN PRESTASI BELAJAR SISWA - Muhtadi; Joko Kristanto; Adibah (Arsy : Jurnal Studi Islam, 2017)
This study aims to determine the correlation of teacher personality and student morals with student achievement in Islamic Junior High School Hidayatul Mubtadiin, Puri District, Mojokerto Regency.This research approach uses quantitative research. The research sample is the entire population of 42 respondents. The data collection instrument used a questionnaire/questionnaire.Based on the calculation of the data analysis above, it is obtained that the value of r Count = 0.031 with N = 100 and the level is obtained by the value of r in the table and compares the probability value of SPSS output with the probability value used by researchers (usually using 5% for social research). The value of rxy r table or SPSS output probability 0.05, then the item is valid. This means that the consequence is that the null hypothesis (Ho) which reads "there is no correlation of the teacher's personality on the morals and learning achievement of the Hidayatul Mubtadiin Puri Mojokerto Middle School students is rejected". On the other hand, the working hypothesis (Ha) which reads "there is a relationship between the personality of the teacher and the morals and learning achievement of students at SMPI Hidayatul Mubtadiin Puri Mojokerto is accepted".